Total phenolic contents, antioxidant activities and organic acids composition of three selected fruit extracts at different maturity Stages - Seri Intan Mokhtar; Pheen Chee Leong; Lee Ee Ven; Nur Ain Abd Aziz (Universiti Malaysia Kelantan, 2014)
The total phenolic contents (TPC), antioxidant activities and organic acid composition of Salacca zalacca, Mangifera indica L. Chok Anan and Baccaurea motleyana Hook. F. extracts at different maturity stages were evaluated by using modified Folin-Ciocalteu assay at 765 nm absorbance, 2,2- diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay and HPLC RP18 column at 215 nm. TPC content ranged from 63.9 mg GAE/100g to 381.23 mg GAE/100g, whereas the antioxidant activity ranged from 3.10% - 84.45%. The M. indica L. Chok Anan contained malic acid and citric acid in the range of 43.897-73.396 mg/100g FW and 2.681-18.428 mg/100g FW at young to ripe stages, respectively. B. motleyana Hook. F. contained citric acid and tartaric acid in the range of 4.649-6.114 mg/100g FW and 3.645-4.365 mg/100g FW at young to ripe stages, respectively. S. zalacca contained malic acid and citric acid in the range of 4.270-17.926mg/100g FW and 0.845-3.284 mg/100g FW at young to ripe stages, respectively. The highest TPC and antioxidant activity were found in the young stage of S. zalacca fruit extract with lowest inhibitory concentration (IC50) valued at 0.57 mgml-1. There was a positive linear correlation between the TPC and antioxidant activities of the fruit extracts. Malic acid is the predominant organic acid in M. indica L. Chok Anan and S. zalacca, while citric acid is the predominant organic acid in B. motleyana Hook. F. This research suggests that the studied fruits at young stage are a better source of TPC and antioxidants. The tested fruits showed a decrease in the concentration of organic acids with ripening.